Collaborative Resilience to Episodic Shocks and Surprises: A Very Long-Term Case Study of Zanjera Irrigation in the Philippines 1979–2010 - Ruth Yabes; Bruce Evan Goldstein (Social Sciences, 2015)
This thirty-year case study uses surveys, semi-structured interviews, and content analysis to examine the adaptive capacity of Zanjera San Marcelino, an indigenous irrigation management system in the northern Philippines. This common pool resource (CPR) system exists within a turbulent social-ecological system (SES) characterized by episodic shocks such as large typhoons as well as novel surprises, such as national political regime change and the construction of large dams. The Zanjera nimbly responded to these challenges, although sometimes in ways that left its structure and function substantially altered. While a partial integration with the Philippine National Irrigation Agency was critical to the Zanjera’s success, this relationship required on-going improvisation and renegotiation. Over time, the Zanjera showed an increasing capacity to learn and adapt. A core contribution of this analysis is the integration of a CPR study within an SES framework to examine resilience, made possible the occurrence of a wide range of challenges to the Zanjera’s function and survival over the long period of study. Long-term analyses like this one, however rare, are particularly useful for understanding the adaptive and transformative dimensions of resilience.